C++ fundamentals I and II - Deitel, Paul J. (LiveLessons., 2011)
"C++ Fundamentals I and II is professional software developers who are not familiar with C++ and object-oriented programming ... The LiveLesson begins with an introduction to core C++ concepts, including classes and objects. Advanced topics follow, including templates, exception handling, inhertiance, polymorphism, and the Standard Template Library (STL)"--Resource description page (viewed June 29, 2011).